The Strategy to Implement Work-Based Learning through Field Work Practices in Vocational High Schools (Multiple Case Studies in Malang Regency and Blitar City) - Defris Hanindya; Yoto Yoto; Amat Nyoto (Journal of Vocational Education Studies, 2021)
This study aims to identify and describe the strategy for implementing work-based learning through fieldwork practices in vocational high schools which include (1) WBL-FWP implementation strategy planning; (2) WBL-FWP implementation strategy; (3) Evaluation of the WBL-FWP implementation strategy; (4) Supporting and inhibiting factors for WBL-FWP Implementation, and (5) Impact on WBL-FWP implementation. This study uses a qualitative approach and the type of research is Multi Cases, the research was conducted at VHS Turen and VHS Islam 1 Blitar. Sources of data were obtained from the principal, vice-principal for public relations, the Chair of the WBL-FWP Working Group, the WBL-FWP Supervisor, and the WBL-FWP Instructor.Â  Collecting data using free and in-depth interviews, study documentation, and observation. The findings show that: (1) WBL-FWP implementation strategy planning is carried out by MoU with linear industry, WBL-FWP supporting industrial practice equipment, and student preparation with WBL-FWP program socialization and debriefing; (2) The WBL-FWP implementation strategy is carried out structurally, the WBL-FWP is implemented for 6 months and there is a pick-up after students complete the WBL-FWP; (3) Evaluation of the WBL-FWP implementation strategy includes the assessment of industrial work results and the assessment of supervisors; (4) The supporting and implementing factors of WBL-FWP are the enthusiasm and full support of all school residents and the limitations of the industry as the location of WBL-FWP, the presence of students to improve products, teachers gain experience and apply learning in schools, and students gain competence in industry; (5) The impact of the existence of WBL-FWP is that the name of VHS will be better known, and students will also gain knowledge outside and know more about how to communicate, socialize with those around them.